Bean weevil Acanthoscelides obtectus (Say) survival and progeny production affected by residual insecticide deposits, and related damage of two types of bean. (September 2022) - Kljajić, Petar; Andrić, Goran; Pražić Golić, Marijana; Jovičić, Ivana
Abstract: The bean weevil, Acanthoscelides obtectus (Say) is a serious pest of stored bean seeds. In an effort to improve current management programs the intention of our study was to assess in the laboratory the impact of insecticide deposits on weevil survival and progeny production after 0, 7, 14, 30, 75, 120 and 165 days of residual activity on beans, and the related bean damage. Two bean types (Gradištanac and Biser) were dusted by malathion (10 mg AI/kg, DP formulation), and treated by water dilutions of spinosad (1 mg AI/kg, SC formulation) and two deltamethrin products, either without the synergist piperonyl butoxide – PBO (0.25 mg AI/kg, SC formulation) or with PBO (0.25 mg AI/kg + 2.25 mg AI/kg, EC formulation). Weevil survival was assessed after 2, 7 and 14 days of exposure and after 0 and 7 days of recovery. Progeny production and damage (kernel damage and weight loss), were assessed after additional 8 weeks. Malathion residual deposits showed the highest effectiveness on survival (no survived weevils), while deltamethrin deposits with PBO were the least effective, i. e at the same level or lower than weevil survival in untreated beans. The highest impact in terms of progeny production and damage were showed by the residual deposits of both deltamethrin formulations (no progeny or damage). In the presence of spinosad and malathion deposits, we recorded low progeny and damage, significantly under the economic threshold. No significant differences between Gradištanac and Biser types were recorded in treatments, while higher progeny and damage we recorded by the control Gradištanac bean than the Biser type, which exceeded economic threshold. Our data show that residual deposits of all tested insecticides on bean kernels demonstrated high control potentials against A. obtectus but deltamethrin deposits, especially with PBO, caused high variation in weevils response. Highlights: Weevil responses to insecticides depend mostly on longevity and duration of exposure to beans. The highest weevil survival was caused by deltamethrin with PBO. Both deltamethrin formulations can prevent weevil progeny and related damage. Spinosad showed high control potential, as well as malathion and deltamethrin. Bean type has no significant effect on weevil survival, progeny and related damage.